2022
DOI: 10.26740/bisma.v14n2.p110-123
|View full text |Cite
|
Sign up to set email alerts
|

Improving company value: the role of human capital, structural capital, capital employed, investment decisions, and manager's attitude to risk

Abstract: Various studies show that companies and organizations have realized that knowledge-based capital is an important company asset. Managing the company's knowledge-based capital is one of the important tasks to encourage companies to compete with other companies. This study aims to identify the knowledge-based capital in human capital, structural capital, and capital employed by companies and its effect on investment decisions that affect company value. Through literature review, this concept also incorporates ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Due to table 2, the results prove that the more organizational capital will increase the value of the company. Organizational capital will affect the increase in the company's ability to create higher profits, so that it can improve the firm value (Sumiati et al, 2022). Organizational capital can increase operational efficiency, because efficient organizational capital will increases productivity and reduces costs with the same result, so as to increase company profits which allows investors to trust the management of the company's working capital (Siti et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to table 2, the results prove that the more organizational capital will increase the value of the company. Organizational capital will affect the increase in the company's ability to create higher profits, so that it can improve the firm value (Sumiati et al, 2022). Organizational capital can increase operational efficiency, because efficient organizational capital will increases productivity and reduces costs with the same result, so as to increase company profits which allows investors to trust the management of the company's working capital (Siti et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Structural capital shows the contribution of structural capital in value creation (Sumiati et al, 2022). Structural capital reflects the company's capabilities that come from systems, strategies, structures, processes, policies, culture, and the company's ability to innovate (Fajarini & Firmansyah, 2012).…”
Section: H2: Human Capital Has a Positive Effect On Firm Valuementioning
confidence: 99%
See 1 more Smart Citation
“…for structural capital, companies can utilize the structural capital contained in intellectual capital to encourage investment decisions in innovation activities in the environment or within the company. [42]. Based on the results of the aforementioned research, it can be concluded that intellectual capital has a positive impact on financial performance.…”
Section: Intellectual Capital On Financial Performancementioning
confidence: 95%